Matrix‐free mass spectrometry imaging of mouse brain tissue sections on silicon nanopost arrays. Issue 13 (5th December 2018) - Fincher, Jarod A.; Dyer, Jacqueline E.; Korte, Andrew R.; Yadavilli, Sridevi; Morris, Nicholas J.; Vertes, Akos
Abstract : Mass spectrometry imaging (MSI) is capable of detection and identification of diverse classes of compounds in brain tissue sections, whereas simultaneously mapping their spatial distributions. Given the vast array of chemical components present in neurological systems, as well as the innate diversity within molecular classes, MSI platforms capable of detecting a wide array of species are useful for achieving a more comprehensive understanding of their biological roles and significance. Currently, matrix‐assisted laser desorption ionization (MALDI) is the method of choice for the molecular imaging of brain samples by mass spectrometry. However, nanostructured laser desorption ionization platforms, such as silicon nanopost arrays (NAPA), are emerging as alternative MSI techniques that can provide complementary insight into molecular distributions in the central nervous system. In this work, the molecular coverage of mouse brain lipids afforded by NAPA‐MSI is compared to that of MALDI‐MSI using two common MALDI matrices. In positive ion mode, MALDI spectra were dominated by phosphatidylcholines and phosphatidic acids. NAPA favored the ionization of phosphatidylethanolamines and glycosylated ceramides, which were poorly detected in MALDI‐MSI. In negative ion mode, MALDI favored sulfatides and free fatty acids, whereas NAPA spectra were dominated by signal from phosphatidylethanolamines. The complementarity in lipid coverages between the NAPA‐ and MALDI‐MSI platforms presents the possibility of selective lipid analysis and imaging dependent upon which platform is used. Nanofabrication of the NAPA platform offers better uniformity compared to MALDI, and the wider dynamic range offered by NAPA promises improved quantitation in imaging. Abstract : Matrix‐free mass spectrometry imaging of brain tissue sections is enabled by laser desorption ionization from silicon nanopost arrays. This platform provides enhanced ionization of certain lipid classes found in mouse brain tissues, and offers molecular coverage complementary to matrix‐assisted laser desorption ionization.